Minimizing the Entropy Penalty for Ligand Binding: Lessons from the Molecular Recognition of the Histo Blood‐Group Antigens by Human Galectin‐3. (17th April 2019) - Gimeno, Ana; Delgado, Sandra; Valverde, Pablo; Bertuzzi, Sara; Berbís, Manuel Alvaro; Echavarren, Javier; Lacetera, Alessandra; Martín‐Santamaría, Sonsoles; Surolia, Avadhesha; Cañada, Francisco Javier; Jiménez‐Barbero, Jesus; Ardá, Ana
Abstract: Ligand conformational entropy plays an important role in carbohydrate recognition events. Glycans are characterized by intrinsic flexibility around the glycosidic linkages, thus in most cases, loss of conformational entropy of the sugar upon complex formation strongly affects the entropy of the binding process. By employing a multidisciplinary approach combining structural, conformational, binding energy, and kinetic information, we investigated the role of conformational entropy in the recognition of the histo blood‐group antigens A and B by human galectin‐3, a lectin of biomedical interest. We show that these rigid natural antigens are pre‐organized ligands for hGal‐3, and that restriction of the conformational flexibility by the branched fucose (Fuc) residue modulates the thermodynamics and kinetics of the binding process. These results highlight the importance of glycan flexibility and provide inspiration for the design of high‐affinity ligands as antagonists for lectins. Abstract : Konformative Präorganisation des natürlichen A/B‐Blutgruppenantigens ist der Ursprung der hochaffinen Interaktion mit humanem Galectin‐3, einem Lectin, das immer mehr Interesse in der Biomedizin findet. Einer Kombination struktureller Techniken zufolge ist der Fucoserest nicht an direkten Kontakten mit dem Protein beteiligt, er moduliert allerdings die Kinetik und Thermodynamik des molekularen Erkennungsprozesses.